Uji Daya Hasil Beberapa Genotipe Tanaman Tomat(Lycopersicumesculentum Mill) di Dataran Rendah - Debby Ester; Adiwirman '; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Tomato plants were one type of horticultural crops those play an important role in the nutritional needs of the community, because it contains vitamins and minerals needed for health.One of the critical success factors of tomato cultivation was the use of high yielding varieties that adapted well to the growth environment.This study aims to obtain best yield of some tomato genotypes that can grow well in the lowlands. This study using a completely randomized block design (CRBD)consisting of 6 treatments and 3 replications, so there are 18 experimental units. The treatmentswere: genotype IPB T64-2-2 (1), IPB T43-6-8, IPB T33-1-3, IPB T30- 4-4, Intan variety, and Karina.The genotypes treatments were significantly affect the plant height, stem diameter, days to flowering, harvesting time, fruit diameter, number of fruit cavities, fruit flesh thickness, number of seeds per gram, weight per fruit, and total weight per plant.The experimental result showed those genotypes IPB T43-6-8 and IPB T33-1-3 has the highest total fruit weight. Genotipe IPB T43-6-8 has a lowest total fruit weight per plant (777.1 g) comparend to Intan and Karina. Keywords:Yield potential, Lycopersicumesculentum, genotype, lowland